Peran Pembelajaran Elektronik terhadap Citra Merek Melalui E-WOM dan Kepuasan Mahasiswa di Era Pandemi Covid-19 - Kristiana Susilowati; Ardianto Ardianto (Jurnal Ilmiah Aset, 2023)
The recent shift to online learning as a result of the COVID-19 outbreak has left universities vying for reputation. This phenomenon is interesting because e-learning offers learning system solutions during a pandemic, which is a fairly effective learning tool without creating crowds of students. Increased competition among tertiary institutions has made every university, including UNKAHA Semarang, challenged to form a positive image in the wider community. Many prospective students will have a special affinity for a university institution that has a positive image. Therefore, a positive image is very important to be researched and always re-evaluated by each tertiary institution. This research concentrates on the relationship and role of e-learning, e-word of mouth, student satisfaction with university brand image at Karya Husada University (UNKAHA) Semarang in the era of the Covid-19 pandemic. This study used a quantitative method by distributing questionnaires to Unkaha students, the data obtained was then processed using the SPSS and Excel programs. The results showed that e-learning had a positive and significant effect on e-wom, student satisfaction had a positive and significant effect on Unkaha's brand image, e-learning had a positive and significant effect on student satisfaction, e-wom played a role in mediating the influence between e-learning and image university brand, and student satisfaction play a role in mediating the influence between e-learning and university brand image.